2007
DOI: 10.1021/ac071513s
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Acceleration Charge Detection Mass Spectrometry:  Application to Weighing Electrosprayed Droplets

Abstract: We describe a new approach to measuring the masses of individual macroions. The method employs a pulsed acceleration tube located between two sensitive image charge detectors. The charge and velocity of the macroion are recorded with the first image charge detector. The ion is pulse accelerated through a known voltage drop, and then the charge and velocity are remeasured using the second image charge detector. The mass of the ion is deduced from its charge and its initial and final velocities. The approach has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…The close agreement between the measurements of ref. 24 and our simulations lends further credence to the accuracy of the scaling laws developed in this paper.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…The close agreement between the measurements of ref. 24 and our simulations lends further credence to the accuracy of the scaling laws developed in this paper.…”
supporting
confidence: 83%
“…We may infer from this that an aerosol resulting from EHD tip-streaming should be roughly as monodisperse as the droplets formed from capillary pinching of tip-streaming jetswhich are quite monodisperse indeed. It also is noteworthy that in a recent experimental study, Mabbett et al (24) measured the charge on electrospray droplets and showed that the distribution of charge on the droplets peaks at ≈ 0:40 Q R . The close agreement between the measurements of ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous single particle charge detection studies have focused on using the signals for mass-to-charge ratio measurements of individual particles (Benner, 1997;Fuerstenau & Benner, 1995;Mabbett, Zilch, Maze, Smith, & Jarrold, 2007;Schultz, Hack, & Benner, 1998). Here we use these signals for measuring the rate at which particles are injected into the vacuum chamber and apply the rates to particle beam characterization.…”
Section: Particle Injection Ratementioning
confidence: 99%